Implementasi Kurikulum Merdeka pada Rumpun Mata Pelajaran Pendidikan Agama Islam - Zakiyah, Himayatuz; Sokip; Khoirul Anam; Liatul Rohmah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research is based on the independent curriculum which has been developed into a more variable curriculum but still focuses on basic materials, character development and student competence. As in his review, the independent curriculum aims to restore the learning crisis which is getting worse due to the pandemic. Apart from that, it also aims to provide freedom to institutions and teachers to develop and manage curriculum and learning that is adapted to the characteristics of educational units and students. This research is descriptive research using a qualitative approach. The results of this research are: 1) Planning for learning tools begins with attending workshops and outreach related to the independent curriculum. Teaching equipment such as material books are taken from the Ministry of Islamic Religion, while accompanying books are from madrasas. 2) Implementation of independent curriculum learning starts from grade 7 first. In formulating the learning objectives of these two madrasas, they analyze the competencies and scope of material on learning outcomes and relate them to the context, the flow of learning objectives is formulated by developing and modifying the examples that have been provided, the differentiated learning of these two madrasas focuses on the content and learning process. 3) learning assessment is carried out by determining the criteria for learning objective requirements (KKTP) based on the learning objectives.